2015
DOI: 10.1080/07315724.2014.926161
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Zinc and Selenium Supplementation on Thyroid Function in Overweight and Obese Hypothyroid Female Patients: A Randomized Double-Blind Controlled Trial

Abstract: This study showed some evidence of an effect of Zn alone or in combination with Se on thyroid function of overweight or obese female hypothyroid patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
2
8

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 49 publications
(78 reference statements)
3
36
2
8
Order By: Relevance
“…72 A recent study demonstrated that 12 weeks of 30 mg zinc supplementation alone or in combination with selenium in overweight or obese female hypothyroid patients significantly increased FT3 levels, and increased the FT3:FT4 ratio. 83 These findings confirm zinc's integral role in T4 to T3 conversion. Interestingly, serum zinc levels did not change throughout the study, consistent with previous studies, 84 suggesting zinc concentrations remain in a normal range during sub-clinical deficiency.…”
Section: Zincsupporting
confidence: 52%
See 2 more Smart Citations
“…72 A recent study demonstrated that 12 weeks of 30 mg zinc supplementation alone or in combination with selenium in overweight or obese female hypothyroid patients significantly increased FT3 levels, and increased the FT3:FT4 ratio. 83 These findings confirm zinc's integral role in T4 to T3 conversion. Interestingly, serum zinc levels did not change throughout the study, consistent with previous studies, 84 suggesting zinc concentrations remain in a normal range during sub-clinical deficiency.…”
Section: Zincsupporting
confidence: 52%
“…The role of zinc in the body is remarkably complex, and its impact on thyroid function includes thyroid hormone production, T4 to T3 conversion, and T3 receptor function. 83 Zinc deficiency has been shown to decrease thyroid hormone availability, with correction of hormone levels noted with zinc supplementation. 72 A recent study demonstrated that 12 weeks of 30 mg zinc supplementation alone or in combination with selenium in overweight or obese female hypothyroid patients significantly increased FT3 levels, and increased the FT3:FT4 ratio.…”
Section: Zincmentioning
confidence: 99%
See 1 more Smart Citation
“…Selenoproteinler, tiroid hormon biyosentezine ve metabolizmasına, antioksidan savunma sisteminin kontrolüne katkı sağlamaktadır. 8 Çinko, tiroid hormonları dahil olmak üzere birçok hormon ve enerji metabolizmasında rol oynayan birçok enzimin aktivitesi için gerekli olan temel eser elementlerden biridir. Çinkonun organizmadaki rolü karmaşıktır, tiroid hormonlarının hem sentezini hem de çalışmasını etkilemektedir.…”
Section: Introductionunclassified
“…Çinkonun organizmadaki rolü karmaşıktır, tiroid hormonlarının hem sentezini hem de çalışmasını etkilemektedir. 8,10 Zn ve tiroid metabolizması arasındaki ilişki T3 reseptörlerinin nükleer Zn-bağlayıcı proteinler içerdiği hipotezine dayanır. Çinko, tiroid hormonlarının ve ilgili reseptörlerin biyolojik işlevi için gereklidir.…”
Section: Introductionunclassified